Research on Music Education from the Perspective of Psychology - Lin, Wang (Journal of Educational Research and Policies, 2026)
Music education plays a certain role in promoting one’s musical cultivation and spiritual culture. Music psychology is a unique method born in the practice of music education. Therefore, music psychology is of great significance for improving music education. Music psychology and music education complement each other, and they have important value in cultivating music majors’ good professional abilities and healthy personalities. The discipline of “music” can play a role that other disciplines cannot in students’ “mental health”. Good music education not only helps improve students’ musical cultivation, but more importantly, it helps students shape a healthy mind.